STRENGTHENING PUBLIC TRUST THROUGH DIGITAL FORENSIC AUDIT: A STUDY OF EMERGING PUBLIC SECTOR ACCOUNTABILITY - Adonia Anita Batkunde; Theresia Febiengry Sitanala (Adisam Publisher, 2025)
This study aims to examine the role of digital forensic audits in strengthening public trust by improving public sector accountability. In the digital era, various public financial management and administration practices are increasingly vulnerable to potential misuse, data manipulation, and fraud that are difficult to detect using traditional audit methods. The advent of digital forensic audits offers a technology-based approach that enables more effective, transparent, and accurate fraud detection, investigation, and prevention. This study employed a literature review method, examining various academic sources, regulations, and best practices across relevant jurisdictions. The results indicate that digital forensic audits can serve as a strategic instrument in building transparency, strengthening oversight mechanisms, and increasing the accountability of state officials in the eyes of the public. However, challenges such as limited competent human resources, uneven technological infrastructure, and a still-developing regulatory framework are major obstacles to widespread implementation. These findings emphasize the importance of strengthening the capacity of public institutions, investing in technology, and harmonizing regulations to ensure the effectiveness of digital forensic audits as a means of strengthening public trust in the public sector.